Klimaresiliens:: Fra handlingsunderskud til institutionsopbygning - Scavenius, Theresa; Lindberg, Malene Rudolf (Slagmark - Tidsskrift for idéhistorie, 2018)
This article addresses resilience in relation to climate change. Currently, our communities are not resilient to climate changes due to a strikingly limited political and scientific framing of climate change as solely a problem of emissions and individual behaviour. Owing to vulgarized interpretations of individual incentives for climate action, contextual barriers to action and the efficiency of individual climate action, this causes an action deficit on both collective and individual levels. We argue that a paradigm shift is needed in order to engage with more adequate academic analysis and efficient policies. This new paradigm should focus on the capacities of societal institutions, which reflect precisely the level of climate resilience in a society. Resilience is not about societal and political immovability when faced with crisis of the dimensions of the climate crisis. It is about changing our society and politics and building institutions that enable us to properly respond to crisis.